Tick Infestation of the Mediterranean Spur-Thighed Tortoises (Testudo graeca, Linnaeus, 1758) from Western Regions of Algeria - Ammar Selles Sidi Mohamed; Mokhtaria Kouidri; Ammar Ait Amrane; Belcacem Belhamiti Tahar; Achour Hamza; Taha Bia (Folia Veterinaria, 2024)
The Spur-thighed tortoise has a large geographic distribution and can be infested by several tick species, mainly Hyalomma aegyptium. This tick has recently been confirmed as a natural carrier of numerous pathogenic, including zoonotic agents. The purpose of this study was to estimate the level of hard tick infestation in Mediterranean tortoises living in some regions of the west of Algeria (Oran, Mostaganem, and Tiaret) during the spring and summer of the year 2019. Among 39 turtles collected from the different study regions, 22 tested positive, which represents an infestation rate of 56.41 %. A total of 224 adult ticks and one nymph were collected, which can display a tick infestation intensity of 10.23 %. All of these ticks belong to a single species, which is Hyalomma aegyptium. In terms of abundance, this study showed 5.78 ticks/tortoise. Regarding sex, we have collected 198 male and 26 female ticks with a sex ratio of 7.62. The preferred attachment sites of Hyalomma aegyptium ticks were the inguinal, the limbs, and to a lesser degree, the neck. A few rare cases have been collected from the carapace. Further studies are needed to assess the impact of the intensity of H. aegyptium infestation on the tortoise’s health status and to assess the potential transmission of zoonotic pathogens.